2014
DOI: 10.2196/mhealth.3359
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Cancer Patients in Illness Management: Usability Evaluation of a Mobile App

Abstract: BackgroundMobile phones and tablets currently represent a significant presence in people’s everyday lives. They enable access to different information and services independent of current place and time. Such widespread connectivity offers significant potential in different app areas including health care.ObjectiveOur goal was to evaluate the usability of the Connect Mobile app. The mobile app enables mobile access to the Connect system, an online system that supports cancer patients in managing health-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 55 publications
9
112
1
Order By: Relevance
“…Our results indicated that the heuristics "consistency and standard" and "recognition rather than recall" have the largest number of violations, with the lowest number of violations related to "error prevention" and "Help users recognize, diagnose, and recover from errors" heuristics. These results are similar to the results of other studies, such as the those conducted by Khajouei et al, Atashi et al, and Nabovati et al in Iran (25)(26)(27), and also the studies conducted by Choi and Bakken, Georgsson et al, Joshi et al, and Mirkovic et al in countries other than Iran, which reported a high number of violations concerning these heuristics (28)(29)(30)(31). On the other hand, the unexpected results of this study indicated that the severity of 60.8% of all violations is major and catastrophic, which accounts for more than half of the identified violations and, in this case, and efficiency of the systems, satisfaction of their users, and hospital's financial issues.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that the heuristics "consistency and standard" and "recognition rather than recall" have the largest number of violations, with the lowest number of violations related to "error prevention" and "Help users recognize, diagnose, and recover from errors" heuristics. These results are similar to the results of other studies, such as the those conducted by Khajouei et al, Atashi et al, and Nabovati et al in Iran (25)(26)(27), and also the studies conducted by Choi and Bakken, Georgsson et al, Joshi et al, and Mirkovic et al in countries other than Iran, which reported a high number of violations concerning these heuristics (28)(29)(30)(31). On the other hand, the unexpected results of this study indicated that the severity of 60.8% of all violations is major and catastrophic, which accounts for more than half of the identified violations and, in this case, and efficiency of the systems, satisfaction of their users, and hospital's financial issues.…”
Section: Discussionsupporting
confidence: 91%
“…Another point noted by the patients was that they did not wish to see too many words in the modules. This is in agreement with previous findings that mobile devices should show limited content and with reduced word count (Mirkovic et al, 2014).…”
Section: User Interface Designssupporting
confidence: 94%
“…Many people, including clinicians, already use mobile devices on a daily basis, including within their clinical practices (Mirkovic et al, 2014). This article reviews the development and use of animation as part of a mobile education tool to enhance the understanding of managing a complex medication regimen within a minority patient population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile apps have been developed to support patients in the various aspects of their involvement in promoting, maintaining and improving health, such as disease prevention, medication adherence, illness management, lifestyle modification and in navigating the health care system including making appointments in health services [4,9,18,19,40,51]. The most common disease-specific apps aim to provide education on diabetes, hypertension and hepatitis [19].…”
Section: The Contribution Of Health Literacy To Digital Health Servicmentioning
confidence: 99%